The effects of healthy ageing on glial cells in the rat spinal cord dorsal horn - Thompson, Aerin Edie (2022)
Ageing leads to greater susceptibility to pain states, but little is known about how changes in glial cells may contribute to this. The aim of the study is to determine how healthy ageing affects glial cells in the key pain processing hub of the spinal cord dorsal horn, through comparing phenotypic features of microglia and astrocyte cell types and their distribution. Lumbar segments L5-6 spinal cord from aged (18–24 months, n=4, male), naïve young-adult (2–3 months, n=4, male), and post-multielectrode array young-adult (2–3 months, n=3, mixed sex) Sprague-Dawley rats were collected and processed using immunohistochemistry directed against glial cells. Our results indicate that with healthy ageing comes decreased cell numbers within the dorsal horn, and also an alteration in activation states. There is a significant reduction in IBA1+ cells with ageing, and a significant increase in area covered by astrocytes with ageing even though the mean grey intensity for both IBA1 and GFAP were not significantly different. Therefore, we conclude that glial cells do undergo changes as a part of healthy ageing. There was an impact on the number of animals and number of experiments conducted due to the COVID-19 pandemic.